Effectiveness of scheduled postoperative intravenous acetaminophen for colon cancer surgery pain - Eiji Horita; Yuji Takahashi; Kojiro Takashima; Kenichiro Saito; Yoshihiro Takashima; Yoshinori Munemoto (BMC, 2018)
Abstract Background Clinical cases are often observed when patients are in need of repeated use of analgesic infusion to manage pain after colon cancer surgery. This paper investigates analgesic frequency as well as safety of postoperative intravenous (IV) acetaminophen in colon cancer surgery where epidural anesthesia is used. Methods Among patients who received epidural anesthesia during colon cancer surgery, one group of twenty eight (28) patients received acetaminophen while another group of patients (30) did not receive it. The groups were analyzed from the surgery day to two days after for the postoperative occurrence and frequency of liver dysfunction in relation to analgesic usage. Results The patient group with acetaminophen infusion significantly reduced the amount of analgesic medication compared to the group without the treatment (p = 0.008). Furthermore there was a significantly larger number of patients in the group receiving acetaminophen treatment with the baseline increase of alanine aminotransferase (p = 0.043). In most of the cases, however, the rate of the increase is mild and the patients did not need medication and subsequently recovered quickly. Conclusions Scheduled IV infusion of acetaminophen after colon cancer surgey is concluded an effective method of pain control and alleviation of postoperative discomfort from the surgery day to two days after the surgery.